Faktor-Faktor Yang Mempengaruhi Pendapatan Asli Daerah Di Kota Batam - Harahap, Baru; Rahmat, Muhammad (LPPM Universitas Putera Batam, 2024)
This research aims to evaluate the effectiveness of billboard tax and its contribution to regional revenue (PAD), especially in the context of regional autonomy, which requires local governments to continuously increase their revenue. One of the efforts to achieve this is by optimizing the collection of local taxes, including billboard taxes. Billboard taxes in Batam City provide a significant contribution to local revenue, although in practice, it has not yet reached its full potential. Additionally, tax targets are often set based on past performance rather than actual potential. This study was conducted from April to July 2019, with the research object being the Regional Revenue Office (Dispenda) of Batam City. The sampling technique used was non-probability sampling, specifically purposive sampling, utilizing financial reports from 2019 to 2023. Data analysis was carried out using multiple regression to test the hypothesis. The results of the analysis showed that, simultaneously, the effectiveness of billboard taxes and their contribution significantly affect regional revenue. Partially, the effectiveness of billboard taxes has a significant relationship with PAD, while the contribution of billboard taxes also significantly influences PAD in Dispenda Batam City.